Students' interpretations of mechanistic language in organic chemistry before learning reactions. Issue 2 (1st March 2017) - Galloway, Kelli R.; Stoyanovich, Carlee; Flynn, Alison B.
Abstract : Research on mechanistic thinking in organic chemistry has shown that students attribute little meaning to the electron-pushing ( i.e., curved arrow) formalism. At the University of Ottawa, a new curriculum has been developed in which students are taught the electron-pushing formalism prior to instruction on specific reactions—this formalism is part of organic chemistry's language. Students then learn reactions according to the pattern of their governing mechanism and in order of increasing complexity. If students are fluent in organic chemistry's language, they should have lower cognitive load demands when learning new reactions, and be better positioned to connect the three levels of chemistry's triplet ( i.e., Johnstone's triangle). We developed a qualitative research protocol to explore how students use and interpret the mechanistic language. Twenty-nine first-semester organic chemistry students were interviewed, in which they were asked to (1) explain a mechanism, given all the starting materials, intermediates, products, and electron-pushing arrows, (2) draw in arrows for a reaction mechanism, given the starting materials and products of each step, and (3) predict the product of a reaction step, given the starting materials and electron-pushing arrows for that step. To investigate the students' ideas about mechanistic language rather than their knowledge of specific reactions, we selected reactions for the interview guide that had not yet been taught. Following transcription, we analyzed the interviews using constant comparative analysis to explore how students used and interpreted the mechanistic language. Four categories of student thinking emerged with electron movement underlying students' thinking throughout the interviews. Herein, we discuss these categories, students' interpretation of the symbolism, connections to learning theory, and implications for teaching, learning, and research.